Application of direct coupling method to design problems of hydrostatic guideways accounting for fluid-structure interactions. (March 2023) - WU, Yangong; Qiao, Zheng; Ge, Hao; Xue, Jiadai; Wang, Bo
Highlights: A practical fluid-structure interaction (FSI) model adopting the direct coupling method to predict the performance of hydrostatic slide carriages is proposed. The model is confirmed to be mesh-independent by meshing with three different densities. The full-size model containing elastic deformation and thin film pressure fields is solved simultaneously, and the specific boundary conditions caused by the orifice are considered and enforced via the root iterative method. The vertical stiffness, deformation, and flow rate of the hydrostatic guideway are evaluated and tested with various oil supply pressures. Compared with the theoretical values without considering deformation, the simulation results take the structural deformation into account and thereby exhibit good agreement with those of the experiment. Based on the proposed FSI model, the orthogonal design method is also employed to analyze the influence of structure geometry, and the carriage slide thickness is introduced as the key influential factor of stiffness. Abstract: The deformation of slide carriages caused by oil pressure produces a substantial effect on the performance of hydrostatic guideways. This paper is aimed to propose a practical fluid-structure interaction (FSI) model adopting the direct coupling method to predict the performance more efficiently. To this end, the full-size model containing elastic deformation and thin film pressure fields is solved simultaneously, and the specific boundary conditions caused by the orifice are considered and enforced via the root iterative method. The model is confirmed to be mesh-independent by meshing with three different densities. Furthermore, the vertical stiffness, deformation, and flow rate of the hydrostatic guideway are evaluated and tested with various oil supply pressures. Compared with the theoretical values without considering deformation, the simulation results take the structural deformation into account and thereby exhibit good agreement with those of the experiment. Based on the proposed FSI model, the orthogonal design method is also employed to analyze the influence of structure geometry, and the carriage slide thickness is introduced as the key influential factor of stiffness.